2013
DOI: 10.1890/12-1958.1
|View full text |Cite
|
Sign up to set email alerts
|

Invasive mammals and habitat modification interact to generate unforeseen outcomes for indigenous fauna

Abstract: Biotic invasions and habitat modification are two drivers of global change predicted to have detrimental impacts on the persistence of indigenous biota worldwide. Few studies have investigated how they operate synergistically to alter trophic interactions among indigenous and nonindigenous species in invaded ecosystems. We experimentally manipulated a suite of interacting invasive mammals, including top predators (cat Felis catus, ferret Mustela furo, stoat M. erminea), herbivores (rabbit Oryctolagus cuniculus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 63 publications
1
71
0
Order By: Relevance
“…There are strong trophic interactions between these ubiquitous species Norbury et al 2013). For example, in mixed podocarp-hardwood forests, reducing stoat numbers had no effect on the density of their prey (rats and mice), but control of possums allowed rats to increase while control of rats allowed mice to increase .…”
Section: Which Pest Species Should Be Targeted?mentioning
confidence: 99%
“…There are strong trophic interactions between these ubiquitous species Norbury et al 2013). For example, in mixed podocarp-hardwood forests, reducing stoat numbers had no effect on the density of their prey (rats and mice), but control of possums allowed rats to increase while control of rats allowed mice to increase .…”
Section: Which Pest Species Should Be Targeted?mentioning
confidence: 99%
“…combined; Norbury et al 2013) and larger endangered skinks (grand skinks and Otago skinks; Reardon et al 2012) at Macraes Flat. The gradient in our skink density estimates, from c. 1200 per ha at the experimental control site to c. 4000 per ha at the fence and removal treatments may therefore result in part from variation in predator management.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies on the New Zealand mainland have shown that removing or excluding mammals can increase the survival and/or abundance of skinks (Oligosoma spp.) (Lettink et al 2010;Reardon et al 2012;Jones et al 2013;Norbury et al 2013Norbury et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these ecological release mechanisms can result in increased predation on indigenous taxa in the managed ecosystem (e.g. Rayner et al 2007;Ritchie & Johnson 2009;Norbury et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Norbury et al (2013) demonstrated mouse population growth after experimental predator removal, but only where grass seed provided ample food for mice. Other studies have attributed mouse population increases to relaxation of interference and/or exploitative competition after removal of ship rats (Rattus rattus) (e.g.…”
Section: Introductionmentioning
confidence: 99%